Amygdala and Dorsal Anterior Cingulate Connectivity during an Emotional Working Memory Task in Borderline Personality Disorder Patients with Interpersonal Trauma History - Krause-Utz, Annegret; Elzinga, Bernet M.; Oei, Nicole Y. L.; Paret, Christian; Niedtfeld, Inga; Spinhoven, Philip; Bohus, Martin; Schmahl, Christian (Frontiers in Human Neuroscience, 2014)
Emotion dysregulation and stress-related cognitive disturbances including dissociation are key features of Borderline Personality Disorder (BPD). Previous research suggests that amygdala hyperreactivity along with a failure to activate frontal brain areas implicated in inhibitory control (e.g., anterior cingulate cortex, ACC) may underlie core symptoms of BPD. However, studies investigating interactions of fronto-limbic brain areas during cognitive inhibition of interfering emotional stimuli in BPD patients are still needed. Moreover, very little is known about how dissociation modulates fronto-limbic connectivity during emotional distraction in BPD. We used Psychophysiological Interaction (PPI) to analyse amygdala and dorsal ACC (dACC) connectivity in 22 un-medicated BPD patients with interpersonal trauma history and 22 healthy controls (HC), who performed a working memory task, while either no distractors or neutral vs. negative interpersonal pictures were presented. A measure of state dissociation was used to predict amygdala as well as dACC connectivity in the BPD group. During emotional distraction, both groups showed disrupted amygdala connectivity with dorsolateral prefrontal cortex, which was more pronounced in the BPD group. Patients further showed stronger amygdala-hippocampus and dACC-insula connectivity during emotional interference and demonstrated a stronger coupling of the dACC with nodes of the default mode network (e.g. posterior cingulate). Dissociation positively predicted amygdala-dACC connectivity and negatively predicted dACC connectivity with insula and posterior cingulate. Our results suggest aberrant connectivity patterns involving brain regions associated with emotion processing, salience detection, and self-referential processes, which may be modulated by dissociation, in BPD. Findings might be related to difficulties in shifting attention away from external (distracting) emotional stimuli as well as internal emotional states in BPD.